The Aesthetics of Uncertainty: Ambiguity and Open Endings in Modern Fiction (International Journal of Food and Nutritional Sciences, 2021)
It is the state of uncertainty that became one of the aesthetic approaches of the contemporary fiction. These are aspects that are generally vague, broken narration, and lapsed ending, unlike the traditional narrative structure which emphasizes on conclusion, moral resolution, and development. More than just a narrative deprivation, the paper will discuss the role of uncertainty as the artistic trick that contributes to a more realistic depiction of the psychological aspect of the work and more socio-historical underbalanced and involves the readers in active interaction. The study uses the theoretical application of the contemporary practices of narrative in the spirit of modernist and postmodern in the espousal of ambiguity, authoritative narration and the reflections of human consciousness of the multifaceted interpretations of the human mind. The article assumes that open-ended narratives help in boosting the interpretation plurality and previews role of the reader in meaning-making crafting fiction into an aesthetic platform of participation.